Zero Waste School - Mira, A.; Matos, M.; Araújo, R.; Dias, S.; Mateus, A.; Pires, F.; Ferreira, J.; Maternidade, J.; Fernandes, W. (Open Schools Journal for Open Science, 2020)
The Zero Waste School project began by identifying the main problem in our school: garbage. This subject was discussed in citizenship classes. We decided that it was necessary a plan to inform the school community, in order to reduce garbage and reuse waste. We asked our partner company Maria Granel for help and it was proposed the implementation of an environmental education project - the Z(h)ero program - with the objectives of helping us to manage waste and transform students and collaborators into change actors at school and around the world.